EFEKTIVITAS KEBIJAKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMPN 2 SUKAMULYA KABUPATEN TANGERANG - Ika Ismayanti (GoAcademica Research dan Publishing, 2021)
This study aims to analyze the effectiveness of online learning during the pandemic at SMPN Sukamulya, Tangerang Regency, and find appropriate strategies so that the Tangerang Regency local government can implement online learning. The method used for this research is descriptive qualitative. The source of data in this study comes from informants who are in direct contact with the policies implemented. The results showed that the effectiveness of online learning policies during the Covid-19 pandemic at SMPN 2 Sukamulya, was influenced by various factors, including the availability of internet networks, teacher competence, supervision, learning motivation for students, special assistance for internet quotas, school eligibility to run online learning policies, regulations to regulate the continuity of learning in virtual classrooms, and the feasibility of using online learning methods according to teachers and parents.